A case against plastics ; Search for Amanda ; swimming babies [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles non-biodegradable waste flowing into the shores of Bataan. A newly born baby in a private hospital disappeared without a trace before she was to go home with her parents. The Lozada School of Swimming teaches babies less than a year old to swim.